Archery after reverse total shoulder arthroplasty - Andrew Lachance; Brandon O'Brien; Margaret E. Jonas; Jesse Constantino; Mira Patel; Anna Moravec; Antonina Calcavecchio; Joseph Y. Choi (Journal of Orthopaedic Reports, 2024)
Background: Archery, a popular recreational activity, puts strain on the shoulder girdle. rTSA indications are expanding, thus it is necessary to further understand return to sports such as archery. Methods: A retrospective chart review was performed on patients undergoing primary rTSA with a minimum of 6-month follow-up. Demographic and surgical data was collected. Return to archery metrics included utilization of vertical vs. crossbow, ability to return to archery, presence of pain and instability during archery, modification of archery technique, and reason for lack of return to sport. VAS and ASES scores were obtained. Results: 13 patients self-reported routinely participating in archery before undergoing rTSA. Seven participants (53.8 %) with a mean age of 69.7 years ( ± 6.32 years), returned to sport postoperatively. Four of these seven participants indicated that they switched to using a crossbow to return to the sport. Average VAS score was 1.85 ( ± 0.34, range 0–6). Only one participant returning to the sport had surgery on their dominant arm. Conclusion: Return to archery following rTSA is possible and more likely if the surgery is performed on the bow arm. Switching from a vertical to a crossbow alongside targeted physical therapy to strengthen the deltoid may help facilitate return to archery postoperatively. Level of evidence: III.